PENGEMBANGAN MEDIA INTERAKTIF MATA PELAJARAN IPAS BERBASIS PBL BERBANTUAN CANVA PESERTA DIDIK KELAS IV SDN 3 MOJOSARI TULUNGAGUNG - Putri Dyah Ayu Nur Evitasari; Frita Devi Asriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological developments have had a significant impact on education, particularly in terms of delivering material and increasing student engagement. Based on observations at SDN 3 Mojosari Tulungagung, IPAS instruction is still dominated by the use of textbooks without variations in learning media, leading students to easily become bored and struggle to understand the material. The effort undertaken is to develop interactive learning media. This study aims to develop interactive learning media based on Canva for the IPAS subject, specifically the “Energy” topic for fourth-grade students. This development uses the Research and Development (R&D) research type with the ADDIE model and produces an interactive media product equipped with animations, audio, and visually appealing designs. The product validation was conducted by media experts and subject matter experts. The media expert validation results achieved an average percentage of 92.5%, and the subject matter expert validation results achieved an average percentage of 90%, both falling into the “highly valid” category. During the implementation phase, the interactive media was tested in a fourth-grade class at SDN 3 Mojosari with 17 students. The applicability of the interactive media was assessed through observation, with the results achieving 100% in the “applicable and no revisions needed” category.